Analisis Motivasi Kerja pada Karyawan PD. XYZ - Zhada, Almira; Wolor, Christian Wiradendi; Marsofiyati, Marsofiyati (Peneliti.net, 2024)
Human resources (HR) are extremely vital to a company's operations in the current era of globalization. In order to create a productive work environment or performance, high motivation is needed given by superiors to subordinates. This requires the company to provide motivation in accordance with the aim of raising the enthusiasm of employees in the work environment in order to achieve the common goals that have been set. The purpose of this study was to analyze the work motivation of employees in PD. XYZ. This research uses qualitative methods with a descriptive approach. Data collection is done by observation, interviews and documentation. Data analysis techniques are carried out by collecting data, reducing data, displaying data, and drawing conclusions. The results of this study say that the motivation of keryawan work in PD. XYZ is already fairly high, but there are several things that cause a lack of enthusiasm at work due to lack of appreciation from superiors even though they have worked optimally